2021
DOI: 10.1371/journal.pone.0244559
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of lifestyle risk factors among adult population in India: A cross-sectional analysis from 2005 to 2016

Abstract: Introduction Individual’s early life style and health behaviors are directly linked to chronic non-communicable diseases. Considering the increased burden of NCDs during the last two decades, the aim of this study is to assess co-occurrence/clustering of lifestyle risk factors and its association with different socio-demographic and economic characteristics among adult men and women in India from 2005–2016. Methods This study utilized the data from the National Family Health Survey 2005–06 and 2015–16 survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 24 publications
(22 reference statements)
2
10
2
Order By: Relevance
“…Atorkey and Owiredua (2021), in their study that identified the clustering of five multiple health risk behaviours, also found that low vegetable and fruit intake and low physical activity cluster together within an individual, whereas smoking tobacco and alcohol consumption co-occur together forming another cluster 18. The pattern of clustering of modifiable risk behaviours could also differ by region and community level, as evident from previous studies 17 19. The clustering of two or more modifiable risk behaviours is of great concern because it can intensify the risk of developing chronic diseases and cardiovascular mortality,20 21 22 and most intervention measures are specific to a single risk factor.…”
Section: Introductionmentioning
confidence: 95%
See 4 more Smart Citations
“…Atorkey and Owiredua (2021), in their study that identified the clustering of five multiple health risk behaviours, also found that low vegetable and fruit intake and low physical activity cluster together within an individual, whereas smoking tobacco and alcohol consumption co-occur together forming another cluster 18. The pattern of clustering of modifiable risk behaviours could also differ by region and community level, as evident from previous studies 17 19. The clustering of two or more modifiable risk behaviours is of great concern because it can intensify the risk of developing chronic diseases and cardiovascular mortality,20 21 22 and most intervention measures are specific to a single risk factor.…”
Section: Introductionmentioning
confidence: 95%
“…16 In a study among the US adults, Leventhal et al (2014) used modifiable risk factors like usage of alcohol, drug, nicotine, current obesity status and weekly physical activity and found that the adult population clusters into five subgroups based on the pattern of these modifiable risk factors. 14 Another study in India by Shaikh and Khan (2021) found that hypertension is more likely to cluster with other modifiable risk behaviours such as smoking, alcohol, chewing tobacco, obesity and unhealthy diets in both men and women. 17 Atorkey and Owiredua (2021), in their study that identified the clustering of five multiple health risk behaviours, also found that low vegetable and fruit intake and low physical activity cluster together within an individual, whereas smoking tobacco and alcohol consumption co-occur together forming another cluster.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
See 3 more Smart Citations